The economy behind the forest: Understanding the effects of hunting and wildlife trade on the Lives of Tambrauw People - Madubun, Rifki Alif Mediaanta; Wurarah, Rully Novie; Bauw, Siti Aisah (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Backgorund: The objective of this study is to assess the usage and economic significance of non-timber forest products (NTFPs) derived from animal hunting and trading in Warmandi Village and Weyaf Village, located in the Tambrauw Regency of Southwest Papua. Method: The research employed a descriptive methodology with a quantitative orientation. The collection of primary data involved the use of observation, interviews, and questionnaires with 13 key respondents who are employed as hunters in the two communities. Findings: The findings revealed that the primary commodities consist of four distinct wildlife species, specifically deer, wild boar, Mambruk birds, and tree kangaroos. The annual economic value of non-timber forest products (NTFPs) derived from wildlife amounted to IDR 175,680,000. Wild boar made the highest contribution, accounting for 61% of the total value, followed by deer at 31%, Mambruk birds at 7%, and tree kangaroos at 1%. Non-timber forest product (NTFP) use is conducted through diverse methods, which encompass the trade of unprocessed, processed, and conserved meat. Game products are sold not only in Tambrauw Regency but also in the markets of Manokwari and Sorong Regencies. Conclusion: This study emphasizes the significance of sustainable management and government oversight in harnessing the economic potential of wildlife non-timber forest products (NTFPs) for the well-being of local populations. Novelty/Originality of this article: By revealing the specific economic value of different wildlife species, this study provides new insights into the importance of sustainable NTFP management in complex socio-ecological contexts.